Asymptomatic bradyarrhythmia and obstructive sleep apnea. Issue 4 (October 2014) - Losurdo, Anna; Vollono, Catello; Mazza, Salvatore; Della Marca, Giacomo
Abstract A 46‐year‐old man underwent a routine medical screening. All the exams were normal, except for a 24‐h electrocardiogram that revealed several episodes of bradyarrhythmia with sporadic, prolonged cardiac sinus pauses during sleep. The man was asymptomatic. A polysomnography revealed episodes of bradyarrhythmia with sinus arrest, associated with obstructive sleep apnea. Continuous positive airway pressure treatment determined an improvement of apneas and bradycardia, but, bradyarrhythmia and sinus pauses, correlated to a short‐lasting cluster of obstructive apneas, persisted. The evaluation of patients with asymptomatic bradyarrhythmias should include assessment of sleep apnea, but the diagnosis of sleep apnea does not exclude an evaluation for pacemaker.